The Effect Of Organizational Climate And Organizational Commitment On Organizational Citizenship Behavior (Ocb) At Bpbd Lebong - Yan Presli; Ahmad Soleh; Ida Ayu Made E.G (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2023)
The purpose of this study was to determine the effect of organizational climate and organizational commitment on Organizational Citizenship Behavior (OCB) of employees at BPBD Lebong. The sample in this study was 36 people consisting of 16 civil servants and 20 honorary people. Data collection using a questionnaire and the method of analysis used is multiple linear regression, determination test and hypothesis testing.The results of the regression equation are Y = 9.470 + 0.421X1 + 0.370X2+ 5,292 (e) meaning that organizational climate and organizational commitment have a positive influence on Organizational Citizenship Behavior (OCB) of employees at BPBD Lebong. This illustrates that if the variables of organizational climate and organizational commitment increase, the Organizational Citizenship Behavior (OCB) of employees will also increase. The result of the determination test is 0.521 or (52.1%). This shows that organizational climate and organizational commitment affect organizational citizenship behavior (OCB) of employees at BPBD Lebong by 52.1%, while the rest (100 - 52.1% = 47.9%) are explained or influenced by other variables that are not researched. Organizational climate and organizational commitment together have an influence on Organizational citizenship behavior (OCB) of BPBD Lebong employees with a significant value of 0.000 less than 0.05. Organizational climate has a positive and significant effect on Organizational Citizenship Behavior (OCB) of employees at BPBD Lebong, because the significant value is 0.009 less than 0.05. Organizational commitment has a positive and significant effect on Organizational Citizenship Behavior (OCB) of employees at BPBD Lebong, with a significant value of 0.014 less than 0.05.